KESANTUNAN BERBAHASA TERHADAP HUBUNGAN KEKERABATAN MASYARAKAT BAROMBONG KOTA MAKASSAR: LANGUAGE POLITENESS TOWARDS KINSHIP RELATIONS IN BAROMBONG COMMUNITY MAKASSAR CITY - Febrina, St Hajrah; M, Asia; Nurhusna (Journal of Applied Linguistics and Literature, 2024)
The aim of this research is to describe forms of politeness and forms of politeness violations in the Makassar language towards kinship relations in the Barombong community of Makassar City. This type of research is qualitative research. Data was collected through the method of listening, being involved, taking notes and recording. This research data is in the form of words, phrases and sentences. The data source for this research is the speech of parents and children. Data analysis was carried out by researching transcription of data recorded during conversations in the field. The next process was data reduction, analyzing data, presenting data and drawing conclusions. The validity of the data is obtained from the triangulation process using the triangulation technique of methods, data sources, observers and theory. The results of the research show that the principles of politeness in language are in the form of (1) maxim of wisdom (2) maxim of acceptance, (3) maxim of praise, (4) maxim of humility, (5) maxim of agreement and (6) maxim of sympathy. The forms of violation of language politeness maxims are (1) wisdom maxim, (2) acceptance maxim, (3) praise maxim, (4) humility maxim, (5) agreement maxim and (6) sympathy maxim